Divulgação científica: produção de vídeos com as crianças para a aprendizagem de ciências no ensino fundamental - Nogueira, Francinaldo Mendes (2014)
This dissertation deals with the possibility of the child make science communication through video production, using the technologies of their daily lives, such as computers and cell phones with digital cameras. This work began from a visit to the Amazon Museum, attended by 30 students of the 5th year. There, the participating students registered the class with the aid of photographs, recordings and footage, to return to school, engaged in studies and discussions with the aim of expanding knowledge. From the learning acquired in this way, produced short videos and socialized with 60 pairs of 3rd and 4th year of elementary school. In the methodological procedure used in this study we chose a qualitative research through field research, combined with participant observation and the wheels of conversations, developed in order to investigate how the production of popular science videos, made with children of primary school, contributes to the learning of science. During the study, we sought to underpin the reflection on the following authors: Bueno (2010), Caldas (2010), Birth (2008), Freire (1983), Gonçalves (2012), Noronha (2011). The analysis points to the possibility of children disseminate science from what you know, using a language easily understood together with the production of videos, configured as a way to teach science in school from an educational vision and not only informative.